Contemporary Topics in Patient Safety Volume 2 - Salen, Philip N.; Stawicki, Stanislaw P. (IntechOpen, 2023)
Providing and enhancing high-quality, safe patient care is both a complex process and essential to healthcare evolution. Ranging from pre-hospital environments to clinical milieus in emergency departments, gastrointestinal procedure units, operating rooms, rehabilitation facilities, and critical care units, every element of complex clinical arenas offers opportunities for improvement, including promoting patient and staff safety, optimizing clinical outcomes, enhancing clinical cooperation between service providers, boosting care efficiency, and reducing excessive costs. This book discusses clinical infrastructures, theoretical advisements, cooperative team-building considerations, and an assortment of clinical principles essential to a better understanding of patient safety in the context of complex clinical care, both in and out of the hospital environment. In addition, this collection outlines strategies important to the effective incorporation of enhanced patient safety protocols and principles that are central to improving healthcare networks and systems. The principles, ideas, and challenges presented in this book apply to both resource-abundant and resource-limited environments as well as to global health networks, which continue to evolve with respect to their own unique challenges, cultures, and other characteristics. This book highlights different modes of healthcare delivery across diverse outpatient, prehospital, and inpatient settings with the aim of improving the patient experience while focusing on safety as an integral component of modern health care. The themes discussed in this volume focus on the core issues of distinguishing and promoting opportunities for the advancement of perpetual improvement of clinical practice among individuals and groups of practitioners as well as the importance of designing and implementing safety-centric institutional processes.